Reprodução da espécie nativa Serrasalmus brandtii (Lütken 1875) e da introduzida Metynnis maculatus (Kner 1858) em resposta à alteração hidrológica no baixo São Francisco - Assis, Daniel Alvares Silveira de (2014)
In the Neotropics, the major fishes reproductive stimuli are rainfall, temperature and flood. Environmental changes caused by humans affects reproduction directly. The aim of this study was to compare the differences in reproductive investment of Serrasalmus brandtii (native) and Metynnis maculatus (introduced) and its relationship with hydrologic modification in an area of Lower São Francisco. Bimonthly samples were conducted from December/2013 to August/2012 in the main channel of the river, between Propriá (SE) and Porto Real do Colégio (AL) with gillnets of different mesh. Rainfall, temperature, elevation and river flow data were also obtained. The specimens were measured, weighed and dissected to characterize the stage of gonadal maturation, gonad, liver and coelomic fat weight to calculate the gonadosomatic (GSI), hepatossomatic and coelomic fat index. A portion of the left ovary was dissociated to calculate fish fecundity and measurement of oocytes. Serrasalmus brandtii (109 females and 102 males) showed no significant difference in the sex ratio, however M. maculatus (166 females and 259 males) exhibited 1.5 males for each female (χ ²: 20.3, p<0.05). The asynchrony between the sexes, absence of reproductive peaks and lack of correlation between GSI and environmental characteristics observed in S. brandtii indicate losses coming from hydrologic modification. The new environment does not seems to have been a barrier in synchrony (Spearman 0.72, p<0.05), and reproductive process of M. maculatus. Environmental pressures and competition with introduced species may have resulted in earlier maturation of S. brandtii (female: 105mm, male: 92mm) to compensate the losses in its population. Despite the similarity in oocyte size among the species, the positive correlation between body size and absolute fecundity (Pearson: 0.608, p<0.05), allowed a greater number of oocytes in S. brandtii (U: 398, p<0.05) due to its larger size. Both species have opportunistic strategy, characterized by medium-sized body and high reproductive output, with fractional spawning, small oocytes and high relative fecundity. The high colonizing ability of M. maculatus allied to river flow changes facilitated its establishment. Preventive measures should be taken to minimize their impacts on native fauna.